Salivary Fluoride and pH Levels After Using Toothbrush With 2-Minute Timer (Prototype Trial) - Prihastari, Lisa; Mardiyah, Farida; Mahda, Mahda; Nabila, Nabila; Andini, Revadilla; Isaputra, Rifqi Ramadheni; Priyadharsini, Sonya (Universitas Muhammadiyah Yogyakarta, 2024)
The recommended tooth brushing duration is 2 minutes to obtain optimal fluoride levels in the mouth. Unfortunately, many people, especially teenagers and children, struggled to comply with the minimum duration. This study developed and tested the effectiveness of a toothbrush with a 2-minute timer prototype. This study determined the gaps and the mean scores of salivary pH, fluoride levels, plaque scores, and the number of Streptococcus mutants between the control group that used manual toothbrushes and the experimental group that used the prototype. A crossover and single-blind method was employed, involving 40 second-grade junior high school students selected using a simple random sampling technique. Data was collected by measuring the pH, fluoride levels, and the number of Streptococcus mutants bacteria in unstimulated saliva. The plaque score was also calculated using the Quigley-Hein modified Turesky plaque index (TMQHPI). The average fluoride level obtained by the experimental group was higher (8.86 ± 1.29) than the one of the control group (1.46 ± 0.44). The Independent T-test showed a significant difference in fluoride levels (p = 0.0001), while no significant difference in salivary was found in pH (p = 0.58) between both groups. The toothbrush with a 2-minute timer prototype developed in this study increased the fluoride levels, preventing dental caries and restoring salivary pH levels.